Magnolia Wu unfolds it all - Miller, Chanel (Philomel Books, 2024)
A self-proclaimed sock detective inside her parents' New York City laundromat, 10-year-old Magnolia Wu and Iris, a new friend from California, set off across the city to solve the mystery of each missing sock, meeting people and uncovering the unimaginable along the way.